The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1172/jci.insight.138576
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MAGEL2 in Prader-Willi syndrome leads to decreased secretory granule and neuropeptide production

Abstract: Prader-Willi syndrome (PWS) is a developmental disorder caused by loss of maternally imprinted genes on 15q11-q13, including melanoma antigen gene family member L2 ( MAGEL2 ). The clinical phenotypes of PWS suggest impaired hypothalamic neuroendocrine function; however, the exact cellular defects are unknown. Here, we report deficits in secretory granule (SG) abundance and bioactive neuropeptide production upon loss of MAGEL2 in humans and mice. Unbiased proteomic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 80 publications
5
81
0
Order By: Relevance
“…42,43 At the cellular level, its loss results in a decreased neuropeptide production and secretory capacity. 12 Moreover, MAGEL2 null new born mice also display poor sucking as PWS infants. 44…”
Section: Magel2mentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 At the cellular level, its loss results in a decreased neuropeptide production and secretory capacity. 12 Moreover, MAGEL2 null new born mice also display poor sucking as PWS infants. 44…”
Section: Magel2mentioning
confidence: 99%
“…A recent report has demonstrated that neurons from PWS patients have decreased secretory granules and neuropeptides production. However, the authors attribute this defect to the MAGEL2 gene 12 . Since PWS T1 have more severe phenotypic traits it is possible that the additional loss of NIPA1 hampers the neuroendocrine maturation and secretion 12 …”
Section: The Genetics Of Pwsmentioning
confidence: 99%
“…MAGEL2 (Melanoma Antigen-subfamily like 2) is another paternally imprinted intronless gene, within the PWS locus ( Figure 1 ) [ 64 , 72 , 105 ]. The human gene encodes a protein of 529-amino acids (525 amino acids in mouse) that displays about 51% sequence similarity to NECDIN, and functions as an E3 ubiquitin ligase enhancer involved in retromer endosomal protein trafficking [ 106 , 107 , 108 ].…”
Section: Magel2mentioning
confidence: 99%
“…In addition, the lack of Magel2 in KO mice was accompanied by reduced levels of several neuropeptides, i.e., oxytocin and orexins. Furthermore, the expression of regulatory proteins that participate in processing and exocytosis of neuropeptides via secretory granules was compromised [ 53 , 71 , 72 ]. Magel2 null mice also revealed higher levels of mTOR and its downstream signaling targets in the hypothalamus [ 68 ].…”
Section: Magel2mentioning
confidence: 99%
“…Schaaf–Yang syndrome is a rare neurodevelopmental disorder that has a strong clinical overlap with PWS [ 249 ]. It is caused by mutations in the MAGEL2 gene, which is located in the PWS critical region on chromosome 15q11.2-q13 [ 250 ] and has a pivotal role in hypothalamic neuroendocrine function [ 251 ]. Rodents with MAGEL2 mutations provide an animal model through which PWS can be investigated.…”
Section: Interventional Studies Of Oxytocin Administration In Humansmentioning
confidence: 99%